Ecuador: social inequality, violence and pandemics - Trujillo Montalvo, Patricio (2024)
In Ecuador, the implementation of neoliberal policies developed in the last two years have systematically decreased the response capacity of the State, which has generated an increase in socio-economic gaps (inequality, poverty and exclusion) in a population majority that is far from the government. the construction of policies that guide the common good. This article analyzes from a comparative perspective (cholera epidemic 1991-COVID-19, 2020) the relationship between social inequality, poverty and the negative effects on vulnerable populations in health crises, placing emphasis on the priorities of governments, whether economic, social or policies. Keywords: violence, disease, poverty, pandemic, neoliberalism.